Trapped in the Past: Memories of Georgian Internally Displaced Persons on the Margins of Society. Issue 3 (18th June 2019) - Toria, Malkhaz; Pirtskhalava, Nino; Kekelia, Elene; Ladaria, Konstantine
Abstract: From the early 1990s through the 2008 "Russo-Georgian war, " waves of armed conflicts in the Abkhazia and South Ossetia/Tskhinvali regions of Georgia forced thousands of residents, mainly ethnic Georgians, to leave their homes. More than two decades of protracted internal displacement, marked by tough economic and social problems, led this vulnerable community to a common trap in reckoning with the past: an overwhelming sense of the fundamental ruptures between the idealized past and current, miserable reality. Failures of the displacement policy and "side effects" of numerous humanitarian aid projects hinder internally displaced persons' social integration and leave them on the margins of Georgian society with almost a singular option: to constantly recall meaningful life in the lost homeland, which they remember as free of ethnic phobias and economic problems. In this article, we suggest that for persons who are internally displaced, memories are defined not only by their past lived experiences and present hardships, but also by the official historical narratives that argue that Georgian-Abkhazian and Georgian-Ossetian "endemic" unity and cohabitation was destroyed by Russian imperial politics. Living in constant pain also narrows the future expectations of the internally displaced persons. However, it is the past and the memories that are supposed to be useful in achieving the utopian dream of a return.